Avaliação do poder de suprimento de potássio de doze unidades de solo dos estados do Piauí, Ceará e Rio Grande do Norte cultivadas com cajueiro - Moreira Filho, Maurício (1994)
Samples at the depths of 0-25, 25-50 and 50-75cm were collected in twelve soil units in the States of Piauí, Ceará and Rio Grande do Norte, cropped with cashew (Anacardium occidentale L.) for the evaluation of the potassium supplying power, exchangeable K, non-exchangeable K, total K, as well as that of the total potassium absorved by the plants. The amount of potassium absorved by plants was evaluated by cropping 2Kg of each soil, the depths being measured in pots, during 240 days, with corn, tomato, sorghum and corn. K-NH4OAc, K-Mehlich and K-boiling HNO3 was measured before and after cropping. Total K was measured only before cropping. The potassium contents absorved by the plants ranged from 1,47 to 52,40mg/100g of soil, the initial potassium exchangeable content being equivalent to 1,2 and 1,1 times. The exchangeable potassium supplied by the NH40Ac in pH 7,0 ranged from 1,17 to 48,97mg/100g of soil. The ammonium acetate produced more K than the Mehlich's solution in soils 10,11 and 12. The potassium contents determined by the boiling HNO31N ranged from 1,95 to 121,21mg/100g of soil and were, respectively, 1,7 and 2,5 times bigger than the initial exchangeable potassium. The non-exchangeable potassium (K-HNO3— K-NH4OAc) ranged from 0,59 to 79,28mg/100g of soil while its cropping contribution ranged from zero to 13,20mg/100g of soil. It was observed that the contribution to the plants of non-exchangeable potassium was 100% in soil 9 and 25% in soil 12. It was further observed that the non-exchangeable potassium determined from the HNO3 was, on the average 5 times bigger than the non-exchangeable potassium absorved by the plants. The contents interval of the total potassium ranged from 50,83 to 586,50mg/100g of soil being equivalent, respectively, to the quantities 43 and 12 times bigger than the initial exchangeable potassium. The correlation coefficients found were of great significance when the chemical extractants were compared among themselves, and these with the potassium supplying power.